Evaluating a bioremediation tool for atrazine contaminated soils in open soil microcosms: The effectiveness of bioaugmentation and biostimulation approaches - Lima, D. (2008)
A previously developed potential cleanup tool for atrazine contaminated soils was evaluated in larger open soil microcosms for optimization under more realistic conditions, using a natural crop soil spiked with an atrazine commercial formulation (Atrazerba FL). The doses used were 20£ or 200£ higher than the recommended dose (RD) for an agricultural application, mimicking over-use or spill situations. Pseudomonas sp. strain ADP was used for bioaugmentation (around 107 or 108 viable cells g¡1 of soil) and citrate for biostimulation (up to 4.8 mg g¡1 of soil). Bioremediation treatments providing fastest and higher atrazine biodegradation proved to differ according to the initial level of soil ontamination. For 20£ RD of Atrazerba FL, a unique inoculation with Pseudomonas sp. ADP (9 ± 1 £ 107 CFU g¡1) resulted in rapid atrazine removal (99% of the initial 7.2 ± 1.6 lg g¡1 after 8 d), independent of citrate. For 200£ RD, an inoculation with the atrazine- degrading bacteria (8.5 ± 0.5 £ 107 CFU g¡1) supplemented with citrate amendment (2.4 mg g¡1) resulted in improved biodegradation (87%) compared with bioaugmentation alone (79%), even though 7.8 ± 2.1 lg of atrazine g¡1 still remained in the soil after 1 wk. owever, the same amount of inoculum, distributed over three successive inoculations and combined with citrate, increased Pseudomonas sp. ADP survival and atrazine biodegradation (to 98%, in 1 wk). We suggest that this bioremediation tool may be valuable for efficient removal of atrazine from contaminated field soils thus minimizing atrazine and its chlorinated derivatives from reaching water compartments.